Mobbing: o bullying corporativo sob uma perspectiva de gestão - Furtado Junior, Evaldo Reis (2011)
This paper aims to investigate the psychological harassment at workplace, making an approach of market aspects that encourage competition and disputes among employees, fertile field for the appearance of mobbing. It also presents the obtained results of a qualitative research, bringing the history of two professionals who suffered the perverse effects of that kind of harassment. Mainly, it is a work focused on the treatment of mobbing under the perspective of management, that is, of ways that can be identified and adopted to combat it. At the end, three management pillars are strategically built as proposal in order to be adopted as preventive measures by managers, directors and/or C.E.O. who seek to minimize the problem.